Hearing level and its relationship with academic performance in students of an educational institution in Lima: Nivel auditivo y su relación con el rendimiento académico en estudiantes de una institución educativa de Lima - Cordero-Pinedo, Félix M. (2023)
Introduction: Hearing is the usual way to acquire language, which allows us the development of thought and knowledge; hearing loss can affect the ability to learn and communicate in children and cause alterations in their behavior and academic performance. Objective: To determine the relationship between hearing level and academic performance in primary school students from a public educational institution in Lima. Methods: Observational, correlational and cross-sectional study. Otoscopy and audiometry were performed in 94 students of the sixth year of primary school of the Santa Rosa de Lima educational institution, in Los Olivos-Lima. Was used the otoscope, the audiometer and the final grades of each student of the first academic semester 2022 as instruments. The relationship was analyzed using Spearman's Rho correlation coefficient. Results: 35.1% of students had mild hearing loss and 64.9% had normal hearing loss. The average academic performance of the sample was 14.74; the average academic performance of the normoacusic students, 14.89 and the average academic performance of the hearing impaired, 14.48. In the Spearman's Rho correlation análisis, it was found a positive correlation between hearing level and academic performance (0.200). Conclusions: There is a positive relationship between hearing level and academic performance in sixth grade students of the Santa Rosa de Lima- Los Olivos educational institution.